Conceptualization about the parent involvement on the teaching-learning process actors - Navarro Saldaña, Gracia; Vaccari Jiménez, Pamela; Canales Opazo, Tatiana (Revista de Psicología, 2001)
To investigate the concept of parent involvement in their children’s education, parents, teachers, and educational authorities were asked to give their views through qualitative methodologies. Participants belong to urban and country schools of the región del Bio Bio.There are differences in the conceptualizations of the board members and the others participants of the study, because they have a point of view more theoretic than who lives the relationship between home school. Other results indicate than the parent involvement should be taken like a threaten by the teachers, and this is still restricted to the instructive aspect from the home to the parents.